Pengaruh Akuntabilitas, Kesesuaian Kompensasi Dan Pengendalian Intern Terhadap Potensi Kecurangan Dana Desa - Melisa Eka Sari; Fefri Indra Arza; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
This research aim to determine the effect of accountability, suitability of compensation and intern control. Type of this research on causality. The population in this study was in village at Lima Puluh Kota.This research uses the total sampling technique so that the entire population in used as the research sample. The data scource is primary data. Methods of collecting data by distributing questionnaires. The result of the research concluded that accountability, suitability of compensation had a significant negative effect and internal control had a significant positive effect on potential fraud.